Detection of the Transposition Property of Genes that Confer Resistance to Antibiotics, Heavy Metals and Minimal Media (M9) - Y. Al-Hayawi, Anas (Tikrit Journal of Pharmaceutical Sciences, 2023)
This study involved fifty four bacterial isolates of different species collected from patients with urinary tract infection in TIkrit city during February-June 2008. Bacterial isolates were identified by using morphological and cultural characteristics and biochemical tests.Results showed that17(31.48%) bacterial isolates were gram negative and the rest were gram positive. The resistant bacterial isolates were examined for 17 antibiotics belonging to various group of antibiotics and also to 5 salts of heavy metals, in addition to the ability of utilize of different sugar as carbon source. These isolates revealed different patterns of resistance and utilizing ability of sugar. Another character of plasmid DNA in the bacterial isolates was investigated. Character of plasmid DNA in bacterial isolates was also included in this study where the transposition property for genes coding for antibiotics and heavy metals resistance and utilizing ability of sugar was detected using the incubation temperature 40 °C to 90 minutes as inducer factor for transposing genes jumping. in this concern results showed that in all isolates genes coding for all antibiotics except (Ciprofloxacin and Nitrofurantion), heavy metal (HgCl2) and sugar (Lactose).